KADAR ENZIM KHOLINESTERASE DARAH PETANI TERPAPAR PESTISIDA YANG DIBERIKAN RIMPANG TEMULAWAK (Curcuma xanthorrhiza Roxb) - Haerul Anam; Nurhidayati Nurhidayati; Maruni Wiwin Diarti; Zaenal Fikri (poltekkes kemenkes mataram, 2015)
Abstract: This study aims to determine the potential use of ginger rhizome (Curcuma xanthorrhiza Roxb) in increasing levels of enzyme kholinesterase on farmers who are exposed to toxic pesticides.The research method used is pre - posttest Control Design. In this research, there are 3 groups of samples each of 30 persons, ie negative control group who did not experience organophosphate and carbamate pesticide poisoning, the positive control group, farmers who suffered pesticide poisoning organophosphates and carbamates but not given the rhizomes of ginger (Curcuma Roxb xanthorrhiza), and treatment groups, farmers who experienced pesticide poisoning were organophosphates and carbamates and ginger rhizome (Curcuma xanthorrhiza Roxb.) Given dose of ginger is 3 grams / day for 9 days. Measurement of blood cholinesterase enzyme levels using tintometer kit. The results are classified on toxin a severe, moderate, mild and not toxin. Result were tested with Wilcoxon Signed Ranks test and Mann-Whitney Test, with 95% confidence level (p 0.05). The research proves that there are significant differences in levels of blood cholinesterase enzyme treatment groups before and after treatment (p 0.05) and no significant differences in levels of blood cholinesterase enzyme treatment group and positive control groups after the study (p <0.05). The conclusion of this study, administration of ginger rhizome (Curcuma Roxb xanthorrhiza) with a dose of 3 grams / day for 9 days can significantly increase levels of plasma cholinesterase enzyme in the farmers who suffered organophosphate pesticide poisoning and Carbamat. Therefore, the researchers recommend that farmers consume a dose of ginger to prevent and reduce organophoshate pesticide poisoning and Carbamat.